VIRTUAL EDUCATIONAL ENVIRONMENTS IN DISTANCE LEARNING FOR GROUND-BASED WEAPONS SYSTEMS - Golovan , Vyacheslav Hryhorovych; Golovan , Artur Vyacheslavovich; Drozdov, Mykhailo Oleksiyovych; Nikul, Stanislav Oleksiyovych (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article reviews the experience of using modern virtual learning environments (VLEs) in the process of distance learning of future specialists in the operation of ground weapons systems. The useful properties of such environments have been identified, in particular, in protected access, centralized storage and modernization of educational and specialized information, the possibility of optimizing collective educational work and its integration with other digital platforms. Particular attention is paid to aspects of information security and potential challenges. A conclusion is drawn regarding the prospects for further development of VLEs in military education.